First Mouse Model for Combined Osteogenesis Imperfecta and Ehlers‐Danlos Syndrome. (June 2014) - Chen, Frieda; Guo, Ruolin; Itoh, Shousaku; Moreno, Luisa; Rosenthal, Esther; Zappitelli, Tanya; Zirngibl, Ralph A; Flenniken, Ann; Cole, William; Grynpas, Marc; Osborne, Lucy R; Vogel, Wolfgang; et al.
ABSTRACT By using a genome‐wide N‐ethyl‐N‐nitrosourea (ENU)‐induced dominant mutagenesis screen in mice, a founder with low bone mineral density (BMD) was identified. Mapping and sequencing revealed a T to C transition in a splice donor of the collagen alpha1 type I (Col1a1) gene, resulting in the skipping of exon 9 and a predicted 18‐amino acid deletion within the N‐terminal region of the triple helical domain of Col1a1. Col1a1Jrt/+ mice were smaller in size, had lower BMD associated with decreased bone volume/tissue volume (BV/TV) and reduced trabecular number, and furthermore exhibited mechanically weak, brittle, fracture‐prone bones, a hallmark of osteogenesis imperfecta (OI). Several markers of osteoblast differentiation were upregulated in mutant bone, and histomorphometry showed that the proportion of trabecular bone surfaces covered by activated osteoblasts (Ob.S/BS and N.Ob/BS) was elevated, but bone surfaces undergoing resorption (Oc.S/BS and N.Oc/BS) were not. The number of bone marrow stromal osteoprogenitors (CFU‐ALP) was unaffected, but mineralization was decreased in cultures from young Col1a1Jrt/+ versus +/+ mice. Total collagen and type I collagen content of matrices deposited by Col1a1Jrt/+ dermal fibroblasts in culture was ∼40% and 30%, respectively, that of +/+ cells, suggesting that mutant collagen chains exerted a dominant negative effect on type I collagen biosynthesis. Mutant collagen fibrils were also markedly smaller in diameter than +/+ fibrils in bone, tendon, and extracellular matrices deposited by dermal fibroblasts in vitro. Col1a1Jrt/+ mice also exhibited traits associated with Ehlers‐Danlos syndrome (EDS): Their skin had reduced tensile properties, tail tendon appeared more frayed, and a third of the young adult mice had noticeable curvature of the spine. Col1a1Jrt/+ is the first reported model of combined OI/EDS and will be useful for exploring aspects of OI and EDS pathophysiology and treatment. © 2014 American Society for Bone and Mineral Research.